The Effect of Family Ownership Concentration and Sustainability Reporting: Does Corporate Governance Matter? - Rohma, Frida Fanani; Bullah, Habi; Chamalinda , Khy’sh Nusri Leapatra; Zulfatillah, Auliya (Universitas Negeri Yogyakarta, 2025)
This research investigates the effect of family ownership concentration and sustainability reporting. Besides, this study also identifies the moderating role of corporate governance on the relationship between those two variables. This study uses a quantitative method using banking industry data listed on the Indonesia Stock Exchange with a total sample during the observation period of 65 data. The existence of special provisions regarding sustainable disclosure makes the banking industry quite representative to be used as a research sample. The results of the study show that the family ownership structure tends to minimize sustainable reporting. Interestingly, most industries in Indonesia are dominated by families, which has the potential to become one of the barriers to foreign investment. The findings of this study indicate that the existence of corporate governance can weaken the influence of family ownership concentration on sustainable reporting. The existence of good governance can be a filter for the negative impact of the concentration of family ownership on sustainable reporting. Keywords: Ownership Structure, Governance, Sustainability Reporting, Families, Opacity ABSTRAK Penelitian ini mengkaji pengaruh konsentrasi kepemilikan keluarga terhadap pelaporan keberlanjutan. Selain itu, penelitian ini juga mengidentifikasi peran moderasi tata kelola perusahaan terhadap hubungan kedua variabel tersebut. Penelitian ini menggunakan metode kuantitatif dengan menggunakan data industri perbankan yang terdaftar di Bursa Efek Indonesia with a total sample during the observation period of 65 data. Adanya ketentuan khusus mengenai pengungkapan berkelanjutan menjadikan industri perbankan cukup representatif untuk dijadikan sampel penelitian. Hasil penelitian menunjukkan bahwa struktur kepemilikan keluarga cenderung meminimalisir pelaporan berkelanjutan. Menariknya, sebagian besar industri di Indonesia didominasi oleh keluarga, yang berpotensi menjadi salah satu hambatan investasi asing. Temuan penelitian ini menunjukkan bahwa keberadaan tata kelola perusahaan dapat memperlemah pengaruh konsentrasi kepemilikan keluarga terhadap pelaporan berkelanjutan. Keberadaan tata kelola yang baik dapat menjadi penyaring dampak negatif konsentrasi kepemilikan keluarga terhadap pelaporan berkelanjutan. Kata Kunci: Struktur Kepemilikan, Tata kelola, Pelaporan Berkelanjutan, Keluarga, Ketertutupan